Estimating the costs of achieving the WHO-UNICEF Global Immunization Vision and Strategy, 2006-2015 - Lara J Wolfson; François Gasse; Shook-P; Patrick Lydon; Ahmed Magan; Abdelmajid Tibouti; Benjamin Johns; Raymond Hutubessy; Peter Salama; Jean-Mari (The World Health Organization, 2008)
OBJECTIVE: To estimate the cost of scaling up childhood immunization services required to reach the WHO-UNICEF Global Immunization Vision and Strategy (GIVS) goal of reducing mortality due to vaccine-preventable diseases by two-thirds by 2015. METHODS: A model was developed to estimate the total cost of reaching GIVS goals by 2015 in 117 low- and lower-middle- income countries. Current spending was estimated by analysing data from country planning documents, and scale-up costs were estimated using a bottom-up, ingredients-based approach. Financial costs were estimated by country and year for reaching 90% coverage with all existing vaccines; introducing a discrete set of new vaccines (rotavirus, conjugate pneumococcal, conjugate meningococcal A and Japanese encephalitis); and conducting immunization campaigns to protect at-risk populations against polio, tetanus, measles, yellow fever and meningococcal meningitis. FINDINGS: The 72 poorest countries of the world spent US$ 2.5 (range: US$ 1.8-4.2) billion on immunization in 2005, an increase from US$ 1.1 (range: US$ 0.9-1.6) billion in 2000. By 2015 annual immunization costs will on average increase to about US$ 4.0 (range US$ 2.9-6.7) billion. Total immunization costs for 2006-2015 are estimated at US$ 35 (range US$ 13-40) billion; of this, US$ 16.2 billion are incremental costs, comprised of US$ 5.6 billion for system scale-up and US$ 8.7 billion for vaccines; US$ 19.3 billion is required to maintain immunization programmes at 2005 levels. In all 117 low- and lower-middle-income countries, total costs for 2006-2015 are estimated at US$ 76 (range: US$ 23-110) billion, with US$ 49 billion for maintaining current systems and $27 billion for scaling-up. CONCLUSION: In the 72 poorest countries, US$ 11-15 billion (30%-40%) of the overall resource needs are unmet if the GIVS goals are to be reached. The methods developed in this paper are approximate estimates with limitations, but provide a roadmap of financing gaps that need to be filled to scale up immunization by 2015.